Linear Dimensional Change and Accu-racy of Fit of Positive Pressure Thermo-Formed Prosthodontic Materials - Zeina M Ahmad; Ahmed A Al-Ali; Omar A Sheet (University of Mosul, College of Dentistry, 2012)
To determine the dimensional accuracy of thermoformed dental base plates. Materials and methods: Six different types of thermoformed materials were used. The circumference of the triangle formed between the index marks on standard maxillary edentulous metal model and measurements of the surface area of the gap between the posterior margin of base plate and the metal model were cap-tured with digital camera and measured with AutoCAD program. Measurements were made after 1 day after processing and then 2, 3 and 7 days. ANOVA and Duncan multiple range test were used to statistical analysis of the data. Results: The linear dimensional shrinkage and inaccuracy of fitness were significant for all of the thermoformed materials. The change after 7 days was not significantly different from that occurred after 1 day. Conclusions: All thermoformed materials exhibited dimen-sional instability, the Duran(hard material) and Durasoft(flexible material) were the most dimensional-ly stable and accurately fitted thermoformed materials.